On functional equations and distributive second order formulae with specialized quantifiers - Movsisyan, Yu. (Algebra and Discrete Mathematics, 2018)
The structure of invertible algebras with distributive second order formulae with specialized quantifiers is given. As a consequence, the applications for solutions of the some functional equations of distributivity on quasigroups are provided.